Prewriting your screenplay : a step-by-step guide to generating stories - Tabb, Michael (Routledge, 2019)
Prewriting Your Screenplay cements all the bricks of a story's foundations together and forms a single, organic story-growing technique, starting with a blank slate. It shows writers how to design each element so that they perfectly interlock together like pieces of a puzzle, creating a stronger story foundation that does not leave gaps and holes for readers to find. This construction process is performed one piece at a time, one character at a time, building and incorporating each element into the whole.The book provides a clear-cut set of lessons that teaches how to construct that story base around concepts as individual as the writer's personal opinions, helping to foster an individual writer's voice. It also features end-of-chapter exercises that offer step-by-step guidance in applying each lesson, providing screenwriters with a concrete approach to building a strong foundation for a screenplay. This is the quintessential book for all writers taking their first steps towards developing a screenplay from nothing, getting them over that first monumental hump, resulting in a well-formulated story conceptthat is cohesive and professional.